Supraglacial lake expansion, intensified lake drainage frequency, and first observation of coupled lake drainage, during 1985–2020 at Ryder Glacier, Northern Greenland - Otto, Jacqueline; Holmes, Felicity A.; Kirchner, Nina (Frontiers in Earth Science, 2022)
Along the Greenland Ice Sheet margin, supraglacial lakes store and redistribute ice sheet surface run off, and comprise an important potential hydrological link between the ice surface and the base, with ramifications for subglacial drainage systems and ice flow. As a consequence of increasing global mean surface air temperatures, these lakes have been predicted to expand further inland and to affect larger areas of the ice sheet. However, as contemporary dynamics of such supraglacial lake expansion are not well studied, any assessment of their future implications remains afflicted with uncertainty. Here, recent changes in supraglacial lake distribution and expansion, and in their drainage behavior and frequency, are presented for Ryder Glacier, Northern Greenland, as concluded from a remote sensing based analysis. The 35-year time span covered in the analysis allows for the detection of trends in lake processes and ice velocity, which otherwise were found to exhibit large inter-annual variability. It also reveals the first occurrence of a coupled lake drainage event in 2002. By linking supraglacial lake expansion, drainage modes, and drainage frequency to the efficiency of the subglacial drainage system and ice flow on seasonal and decadal timescales, a contribution is made to better understand the complexity of coupled glacio-hydrological processes, and to help reduce uncertainties in predictions of future mass loss from the Greenland Ice Sheet.